Bayesian estimation and prediction for Burr‐Rayleigh mixture model using censored data. (25th July 2019) - Noor, Farzana; Sajid, Ahthasham; Shah, Syed Bilal Hussain; Zaman, Mehwish; Gheisari, Mehdi; Mariappan, Vinayagam
Summary: In this study, Burr‐XII and Rayleigh distributions are combined to form a new mixture model that is considered to model heterogeneous data. Our objective is to estimate parameters of the proposed mixture model using Bayesian technique under type‐I censoring. Bayesian parameter estimation for the said mixture model is conducted by using informative priors, ie, gamma and squared root inverted gamma (SRIG) as well as noninformative prior, ie, Jeffrey's prior. Squared error loss function (SELF) and quadratic loss function (QLF) are employed to obtain and Bayes estimators. Properties of the proposed Bayes estimators are highlighted through a simulation study. When prior distributions and loss functions utilized in the study are compared in terms of posterior risks, informative prior found to be more suitable and decision turns out to be in favor of QLF. Prediction limits for the single sample case and two sample case are obtained to provide an insight into future sample data. Application of the proposed model is also elaborated using a real‐life example. Abstract : In this article, a type‐II mixture model has been developed in order to model heterogeneous lifetime data. Bayesian estimation of the parameters has been obtained using type‐I right censoring, and prediction for future samples has been provided. Study suggests the proposed model as an efficient alternative to existing lifetime mixture models.